2016
DOI: 10.1523/jneurosci.0744-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Catecholaminergic Neuromodulation Shapes Intrinsic MRI Functional Connectivity in the Human Brain

Abstract: The brain commonly exhibits spontaneous (i.e., in the absence of a task) fluctuations in neural activity that are correlated across brain regions. It has been established that the spatial structure, or topography, of these intrinsic correlations is in part determined by the fixed anatomical connectivity between regions. However, it remains unclear which factors dynamically sculpt this topography as a function of brain state. Potential candidate factors are subcortical catecholaminergic neuromodulatory systems,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
72
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 71 publications
6
72
3
Order By: Relevance
“…Importantly, the observed spatial correspondences between the structural and functional topography of the mouse connectome argue for a critical role for these neuromodulatory nuclei in shaping large-scale neural activity. This notion is consistent with the observation that catecholaminergic and serotonergic activity critically control functional network topography and dynamics 30,31,49 . Together with the observation that connector hub removal critically diminishes network communicability, these results suggest that that ascending modulatory systems are strategically wired as central orchestrators of large-scale inter-modular communication, a network property that might be key in ensuring the effective and finely-tuned control of complex behavioral and physiological states exerted by these systems.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Importantly, the observed spatial correspondences between the structural and functional topography of the mouse connectome argue for a critical role for these neuromodulatory nuclei in shaping large-scale neural activity. This notion is consistent with the observation that catecholaminergic and serotonergic activity critically control functional network topography and dynamics 30,31,49 . Together with the observation that connector hub removal critically diminishes network communicability, these results suggest that that ascending modulatory systems are strategically wired as central orchestrators of large-scale inter-modular communication, a network property that might be key in ensuring the effective and finely-tuned control of complex behavioral and physiological states exerted by these systems.…”
Section: Discussionsupporting
confidence: 91%
“…Of note, the high correspondence between functional and structural modules supports a role for connector nodes as strategic orchestrators of brain-wide network activity 29 . In the light of this, our observations suggests that ascending modulatory system are strategically wired as key orchestrators of inter-modular activity, a finding consistent with emerging evidence pointing at a pivotal contribution of cathecolaminergic neurotransmission in modulating functional network activity and dynamics 30,31 .…”
Section: Ascending Modulatory Nuclei Are Configured As Between-networsupporting
confidence: 86%
“…Furthermore, a resting state fMRI study in healthy subjects reported a FC decrease induced by atomoxetine, i.e. a relatively selective NET blocker, predominantly in the posterior brain regions including the visual system [78]. Another fMRI study using a n-back task in healthy volunteers reported atomoxetine-induced FC changes in the frontoparietal network, including areas such as the precentral gyrus and the precuneus, during working-memory processing [79].…”
Section: Discussionmentioning
confidence: 99%
“…Fewer studies have assessed catecholaminergic modulation of large-scale brain network 761 dynamics. Pharmacological fMRI studies in monkeys and humans have shown that catecholamines 762 alter the strength of correlations between distant brain regions (Hermans et al, 2011;Guedj et al, 763 2016;van den Brink et al, 2016;Warren et al, 2016;Hernaus et al, 2017). While 'resting-state' 764 studies have reported catecholamine-induced decreases in correlation strength (van den Brink et al, 765 2016;Guedj et al, 2017), task-based studies have reported increases Hernaus et 766 al., 2017), or the converse for noradrenergic antagonism (Hermans et al, 2011).…”
mentioning
confidence: 99%